Análisis Multitemporal De La Dinámica Fluvial Del Abanico Del Río Guayuriba En La Ciudad De Villavicencio Y Acacías, Meta - Barrera Pongutá, Jairo Arturo (Universidad Antonio Nariño, 2024)
The study focused on analyzing changes in the fluvial dynamics of the Guayuriba River and its floodplain between 2017 and 2023. Landsat 8 and 9 satellite images were used, and spectral indices like NDWI and BSI were applied to assess water and exposed soil. Radiometric and geometric corrections were conducted to enhance image quality.